ECONOMIC SECURITY OF RUSSIA: A RENAISSANCE OF SYSTEMS APPROACH - A. I. Selivanov (Финансы: теория и практика, 2017)
The article describes the wave-like interest in the problem of ensuring Russia’s economic security, and points to the presence in the country of a strong political, business and criminal lobby that is not interested in the civilized legal development of Russia, scientific management and national economic security. It examines different definitions of the concept of economic security and suggests a definition based on integrated approach including assessment of such items as vital infrastructure potential, type of environment, a set of tools, activities and resources. The work considers factors and threats that influence economic security; the methodology for determining threshold values as well as points out that contribution of the Financial University in this area is valuable. The author substantiates the necessity to widely apply scientific tools, especially in the field of strategic management in order to ensure economic security of the country, as well as defense of its national economic interests and sovereignty.